Cyclic Operation Strategies in Trickle Beds and Electrical Capacitance Tomography Imaging of Filtration Dynamics - Hamidipour, Mohsen; Larachi, Faïçal; Ring, Zbigniew (Industrial & engineering chemistry research, 2010)
The dynamics of propagating liquid pulsations generated via various cyclic operation strategies in trickle beds was monitored through electrical capacitance tomography (ECT) for gas and liquid superficial velocities in the range of trickle flow regime. The characteristics of ON−OFF liquid, ON−OFF gas, and gas/liquid alternating cyclic operations were compared in terms of mean liquid holdup, pressure drop, pulsation intensity, pulsation propagation velocity, and spatial maldistribution maps of liquid holdup and liquid pulsation propagation velocity. The morphological features of liquid holdup pulsations as a function of cycle frequency were characterized in terms of breakthrough, plateau, and decay times. Gas/liquid alternating cyclic strategy was shown to produce long-lived liquid pulsations under the applied operating conditions and thus could be viewed as a new process intensification means to achieve uniform phase holdup and velocity distributions. In ON−OFF liquid cyclic operation, pulsation velocity did not increase along the bed unlike the ON−OFF gas and gas/liquid alternating cyclic modes where increased pulsation velocities were able to give rise to pulse flow regime. The gas/liquid alternating cyclic operation resulted in the shortest breakthrough and decay times and the longest plateau time, thus approaching the ideal square-shaped inlet pulsations for symmetrical splits. ECT imaging was also used to scrutinize the dynamics of local deposition of fines in trickle beds fed with kaolin suspensions under the three cyclic operations. Data revealed that applying ON−OFF gas and gas/liquid alternating cyclic methods resulted in significant reduction of fines deposition. This suggests new practical solutions for possible industrial implementation of self-cleaning modulation strategies of trickle beds subject to unwanted filtration during suspension flows.